Central Bank of Iraq Initiative and their Role in Developing ‎Private Industrial Sector - Alzubaidi, Meena Ali Abdulmuhsin Alzubaidi; Karim Bureihi , Faris (Journal of Economics and Administrative Sciences, 2024)
The research sample is the Iraqi Central Bank. It aims to identify the initiatives of the Iraqi Central Bank, indicating loan size and financial allocations provided to the private industrial sector, besides learning this sector’s contribution to the national economy after implementing these initiatives to address the research problem, which is that the private industrial sector suffers from many problems and difficulties, the most important of which is the financing problem for economic reasons, and here comes the role of the Central Bank of Iraq through its initiatives in supporting the economic sectors including the private industrial sector. The research is based on the hypothesis that the Iraqi Central Bank, through its initiatives, has a role in supporting and developing the private industrial sector and enabling it to achieve its desired goals. The researcher used ratios and indicators to evaluate the Iraqi Central Bank initiatives, including the allocation implementation percentage indicator granted from the total number of projects initiatives and loans granted from expenses to finance private industrial projects, and the private industrial sector contribution percentage to the gross domestic production, also the growth rate granted to banks annually and the percentage of initiatives of the private industrial sector contribution to the gross domestic production with its contribution to providing job opportunities. Significant main results of the study are: As a result of the increase in demand by project owners for loans from the Central Bank of Iraq initiative, must continue to increase financial allocations for this initiative and provide all necessary facilities to facilitate the borrowing process. Paper Type: Research paper